2017
DOI: 10.1038/cddis.2016.481
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis gingipains cause defective macrophage migration towards apoptotic cells and inhibit phagocytosis of primary apoptotic neutrophils

Abstract: Periodontal disease is a prevalent chronic inflammatory condition characterised by an aberrant host response to a pathogenic plaque biofilm resulting in local tissue damage and frustrated healing that can result in tooth loss. Cysteine proteases (gingipains) from the key periodontal pathogen Porphyromonas gingivalis have been implicated in periodontal disease pathogenesis by inhibiting inflammation resolution and are linked with systemic chronic inflammatory conditions such as rheumatoid arthritis. Efficient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…P. gingivalis pathogenicity is related to the production of virulence factors including biofilm formation, several varieties of lipopolysaccharide and a family of proteases known as the gingipains, many of which play a role in the development and progression of periodontal disease [29,30]. In addition, in rodent models this bacteria has been associated with promoting a dysbiotic micro-flora and propagating a hyper-inflammatory process [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…P. gingivalis pathogenicity is related to the production of virulence factors including biofilm formation, several varieties of lipopolysaccharide and a family of proteases known as the gingipains, many of which play a role in the development and progression of periodontal disease [29,30]. In addition, in rodent models this bacteria has been associated with promoting a dysbiotic micro-flora and propagating a hyper-inflammatory process [31,32].…”
Section: Discussionmentioning
confidence: 99%
“… Li et al (2013) demonstrated that P. gingivalis is able to reduce the expression of MIF mRNA in deep-pocket tissues ( Li et al, 2013 ). Furthermore, in vitro experiments demonstrated that treatment of macrophages with the lysine-specific gingipain Kgp impaired its migration to apoptotic neutrophils and reduced the anti-inflammatory effect of apoptotic cells, resulting a rapid inflammatory response, leading the authors to suggest that P. gingivalis promotes chronic inflammation by a gingipain-mediated defect in apoptotic cell clearance and resolution of tissue restoration ( Castro et al, 2017 ).…”
Section: Host–pathogen Interaction and Molecular Effects On Host Cellmentioning
confidence: 99%
“…[40,41] Porphyromonas has also been implicated as an activator of both complement and the Th17 axis in chronic periodontitis, a mucosal disease featuring biofilm formation similar to HS. [44] Bacterial species can also directly activate C3aR1 and C5aR1 receptors via the action of PAMPs and DAMPs through direct cell contact. [44] Bacterial species can also directly activate C3aR1 and C5aR1 receptors via the action of PAMPs and DAMPs through direct cell contact.…”
Section: A and C 5a Pathways Are Ac Tivated By Pep Tinophilus Anmentioning
confidence: 99%